Developments in active noise control sound systems for magnetic resonance imaging - Chambers, John; Bullock, Dave; Kahana, Yuvi; Kots, Alexander; Palmer, Alan (Applied acoustics, 2007)
Magnetic resonance imaging (MRI) scanners can produce noise measuring over 130 dB SPL. This noise stimulates the auditory nervous system, limiting the dynamic range for stimulus driven activity in functional MRI (fMRI) experiments and can influence other brain functions. Even for structural scans it causes subject anxiety and discomfort in addition to the impediment to communications. Here we describe the realization and validation of a sound system for sound presentation inside an MRI scanner and the modifications to a standard active noise control technique for use in the noisy and compact environment of the scanner. This paper provides a review of the technology available for the presentation of audio stimuli in an MRI environment and the modifications required for the active control of scanner noise. Some of the content has been previously published [Chambers J, Akeroyd MA, Summerfield AQ, Palmer AR. Active control of the volume acquisition noise in functional magnetic resonance imaging: method and psychoacoustical evaluation. J Acoust Soc Am 2001;110(6):3041–54; Levitt H. Transformed up–down methods in psychoacoustics. J Acoust Soc Am 1971;49:467–77], but this paper goes further in describing the stages of development as the system performance was optimised. The performance of the system and both the objective and subjective reduction of the scanner noise are reported. Finally, we discuss recent improvements to the system that are currently being evaluated and describe the theory of opto-acoustical transducers that operate on the principle of light modulation. These are immune from, and do not create, electro-magnetic interference (EMI) and radio-frequency interference (RFI).